2019
DOI: 10.1097/qad.0000000000002240
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase polymorphism Val158Met is associated with distal neuropathic pain in HIV-associated sensory neuropathy

Abstract: Background: Many of those aging with HIV suffer from distal neuropathic pain (DNP) due to HIV-associated sensory neuropathy (HIV-SN). Prior studies have linked chronic pain conditions to a variant of the catechol-O-methyltransferase (COMT), Val 158 Met. This variant confers reduced enzymatic activity and results in higher synaptic dopamine levels. Here we examined the role of Val 158 Met as a predictor of DNP in HIV-SN. Methods: In 1044HIV-infected individuals enrolled in CNS HIV Antiretroviral Therapy Effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Since it was the village with the lowest level of mercury and cases exceed the reference limit (≥6.0 µg/g), we hypothesize that the presence of the variant ALAD allele influences the occurrence of these disturbances by increasing the association between ALAD protein and Hg molecules and, consequently, raising blood Hg levels. Nevertheless, in addition to the ALAD polymorphism, there may be other genetic influences, making individuals more predisposed to certain conditions influencing the occurrence of neurological symptoms [38][39][40][41][42]. Visual field defects, for instance, have already been associated with a mutation on the OPA 1 (OPA1 Mitochondrial Dynamin Like GTPase) gene [39] and a polymorphism near the TGFBR3 (Transforming Growth Factor Beta Receptor (3) gene [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it was the village with the lowest level of mercury and cases exceed the reference limit (≥6.0 µg/g), we hypothesize that the presence of the variant ALAD allele influences the occurrence of these disturbances by increasing the association between ALAD protein and Hg molecules and, consequently, raising blood Hg levels. Nevertheless, in addition to the ALAD polymorphism, there may be other genetic influences, making individuals more predisposed to certain conditions influencing the occurrence of neurological symptoms [38][39][40][41][42]. Visual field defects, for instance, have already been associated with a mutation on the OPA 1 (OPA1 Mitochondrial Dynamin Like GTPase) gene [39] and a polymorphism near the TGFBR3 (Transforming Growth Factor Beta Receptor (3) gene [38].…”
Section: Discussionmentioning
confidence: 99%
“…Visual field defects, for instance, have already been associated with a mutation on the OPA 1 (OPA1 Mitochondrial Dynamin Like GTPase) gene [39] and a polymorphism near the TGFBR3 (Transforming Growth Factor Beta Receptor (3) gene [38]. Another example is the COMT gene (Catechol-O-Methyltransferase), whose SNPs have been associated with lower chances of developing memory impairment [41] and higher odds of developing distal neuropathic pain [40]. A review study published in 2020 showed that epigenetic alterations such as miRNA expression and DNA methylation could cause impaired memory and neuronal development, depression-like behavior, visual deficits, and hyperactivity, in experimental models [42].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several candidate genes, GCH1 [77], IL6 [78], IL10 and IL1R2 [79], TNFA [80], SCN9A [81], CACNG2 [82], SLC6A4 [83], ACO1 , B2M , BMP6 , TF , CP , TFRC , FXN , and SLC11A2 [84], and HTR2A [85,86] found to be associated with neuropathic pain susceptibility in a single study each. Studies have also reported the association of COMT [74], OPRM1 [86], MMP1 [87], KCNS1 [88], TNFA [89], and P2RX7 [90] harbouring variants with increased pain intensity. The most recent study replicated only one variant in P2RX7 associated with neuropathic pain in patients with herpes zoster [91].…”
Section: Genetic Studies Of Neuropathic Painmentioning
confidence: 99%
“…[91] However, a recent study (n=590) reported that a COMT variant confers an increased risk of distal neuropathic pain in HIV-SN patients of European and African ancestry. [96] Moreover, COMT variants were also associated with pain intensity in patients who underwent lumbar discectomy. [71] Similarly, studies have reported the association of OPRM1 variants with neuropathic pain susceptibility inconsistently in different populations.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%